COURSES ON SHEVCHENKO STUDIES AT CHERNIVTSI UNIVERSITY (THE SUBSTANTIVE SCOPE OF THE PROGRAMS) - КОВАЛЕЦЬ, Лідія (Київський національний університет імені Тараса Шевченка, 2024)
The article examines the peculiarities of teaching philological courses on Shevchenko studies at Chernivtsi University. To this end, the historical experience connected with the pedagogical activity here since 1885 of Prof. S. Smal-Stotskyi is actualized, in particular his introduction of an original method in working with gifted students, which consisted in a hermeneutic approach to understanding the works of T. Shevchenko. Thanks to these efforts, an entire scholarly center in Shevchenko studies emerged at that time. It is stated that for subsequent generations of faculty at the Department of Ukrainian Literature at the mentioned university, Shevchenko studies has also always been a priority in research and research methodology, which has facilitated the engagement of participants in the educational process. Within the current programs for bachelor's degrees in "Secondary Education (Ukrainian Language and Literature)" and "Philology" in Chernivtsi, T. Shevchenko is most extensively covered in the courses "History of Ukrainian Literature of the First Half of the 19th Century", "Studying the Life and Works of Taras Shevchenko in Secondary Schools", "Literary and Artistic Shevchenko Studies Around the World", while the master's program in Philology also includes a separate course "Bukovynian Shevchenko Studies in Names". The substantive content of the work programs of these disciplines is analyzed, as is the broad range of relevant lecture and practical work with students; some topics for discussion are illustrated at the level of specific questions, tasks, methodologies for working on them, etc. Consideration is also given to the peculiarities of independent and individual work in the process of mastering these courses, which also involves developing interests in T. Shevchenko among his young researchers. The study of T. Shevchenko during classes is supplemented by students' individual scholarly work on Shevchenko studies in the form of term papers and master's theses, as well as the annual, now traditional, competitions in declaiming Shevchenko's poetry, and more. An exchange of experience is initiated among higher education professionals in teaching T. Shevchenko. ___________ References Levkulych, V. (2022). Higher education in the mirror of challenges and alternatives of modernity. Philosophy of Education, 28(1), 139-158 [in Ukrainian]. Morenets, V. (2017). Literature and ideology. In V. Morenets (ed.), Literature and ideology: A collective monograph. NaUKMA, 4-12 [in Ukrainian]. Working programs and syllabi of academic disciplines. Faculty of Philology [in Ukrainian]. http://philology.chnu.edu.ua/?page_id=5912 [in Ukrainian] Smal-Stotskyi, S. (2003). T. Shevchenko. Interpretations / foreword, general editing, notes V. Pakharenko. Brama, 376 p. [in Ukrainian].

У статті розглядаються особливості викладання в Чернівецькому університеті філологічних дисциплін шевченкознавчої тематики. З цією метою актуалізовано історичний досвід, пов’язаний із педагогічною діяльністю тут від 1885 р. проф. С. Смаль-Стоцького, запровадження ним у роботі з обдарованими студентами оригінальної методи, яка полягала в герменевтичному підході до розуміння творів Т. Шевченка. Завдяки цим зусиллям постав тоді цілий науковий осередок у шевченкознавчій науці.  Сконстатовано, що для наступних поколінь працівників кафедри української літератури вказаного університету так само завжди була в пріоритеті шевченкознавча наукова й науково-методична тематика, що й розгортало можливості прилучення до неї учасників освітнього процесу. В рамках чинних нині програм із підготовки бакалаврів за спеціальностями «середня освіта (українська мова та література)» і «філологія» у Чернівцях про Т. Шевченка найбільше говорять у курсах «Історія української літератури першої половини ХІХ ст.», «Вивчення життя і творчості Тараса Шевченка в ЗЗСО», «Літературно-мистецька Шевченкіана світу», тоді як магістерська програма спеціальності «філологія» включає ще й окремий курс «Шевченкознавство Буковини в іменах». Проаналізовано змістове наповнення робочих програм указаних дисциплін, широку проблематику відповідної лекційно-практичної роботи зі студентами, окремі теми для обговорення проілюстровано на рівні конкретних запитань, завдань, застосовуваної методики їхнього опрацювання тощо. Зважено також на особливості самостійної та індивідуальної роботи в процесі опанування курсів, що так само передбачає розвиток зацікавлень Т. Шевченком з боку його молодих дослідників. Вивчення Т. Шевченка під час занять доповнюється індивідуальною науковою роботою наших студентів на шевченкознавчу тематику у форматі курсових та магістерських досліджень, щорічними – вже традиційними – конкурсами декламаторів Шевченкової поезії тощо. Зініційовано обмін досвідом між працівниками вищої школи у викладанні Т. Шевченка. ____________ Список використаних джерел Левкулич, В. (2022). Вища освіта у дзеркалі викликів та альтернатив сучасності. Філософія освіти, 28(1), 139-158. Моренець, В. (2017). Література та ідеологія // Література та ідеологія: колективна монографія / наук. ред. та упоряд. В. Моренця. НаУКМА, 4-12. Робочі програми й силабуси навчальних дисциплін. Філологічний факультет. URL: http://philology.chnu.edu.ua/?page_id=5912 (дата звернення: 24.03.2024 р.) Смаль-Стоцький, С. (2003). Т. Шевченко. Інтерпретації / передм., заг. редагування, примітки В. Пахаренка. Брама, 376 с.
НАВЧАЛЬНІ ДИСЦИПЛІНИ ШЕВЧЕНКОЗНАВЧОЇ ТЕМАТИКИ В ЧЕРНІВЕЦЬКОМУ УНІВЕРСИТЕТІ (ЗМІСТОВИЙ ОБШИР ПРОГРАМ)
Keywords: studying Shevchenko; teaching Shevchenko; S. Smal-Stotskyi; university courses on Shevchenko studies; Chernivtsi University; вивчення Шевченка; викладання Шевченка; С. Смаль-Стоцький; університетські навчальні дисципліни шевченкознавчої тематики; Чернівецький університет